From Ghost Games to the Return of the Crowd: Effects of Increased Fan Attendance During and Following COVID-19 on Home Advantage in the German Soccer Bundesliga - Nufer, Gerd; Stickel, Aisha (American Journal of Management, 2025)
While prior studies have analyzed the effects of COVID-19-induced ghost games on home advantage in Germany’s Soccer Bundesliga, none have examined the 2021/22 season—the period immediately following spectator-free matches. This study addresses that gap by analyzing the impact of fan return on home advantage. Using a dataset of all Bundesliga matches from 2017/18 to 2021/22 (N = 1,530), we performed regression analyses incorporating a categorical variable to represent different phases of attendance restrictions. In the 2021/22 season, after a brief phase of stricter capacity limits, we find evidence of a significantly greater home advantage compared to pre-pandemic levels. However, this elevated effect diminishes over time despite rising spectator numbers. The findings highlight the psychological impact of fans on home team players as the primary mechanism driving home advantage. This suggests that fan presence influences mental rather than physical performance. Accordingly, clubs should prioritize players’ physical and mental well-being, even outside extraordinary contexts such as the pandemic.